2020
DOI: 10.1101/2020.12.22.423940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence for human monocyte-derived macrophage infection and antibody-mediated enhancement of SARS-CoV-2 infection

Abstract: Vaccines are essential to control the spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and to protect the vulnerable population. However, one safety concern of vaccination is the possible development of antibody-dependent enhancement (ADE) of SARS-CoV-2 infection. The potential infection of Fc receptor bearing cells such as macrophages, would support continued virus replication and inflammatory responses, and thereby potentially worsen the clinical outcome of COVID-19. Here we demonstrate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…TMPRSS2 is the principal protease that cleaves the S2’ Spike site required for fusion, but other proteases such as TMPRSS4 and TMPRSS11 may also function in that role 26,27 . Nevertheless, the lack of infection in our model argues against alternative entry pathways, and is consistent with findings reported by others using different macrophage cell models 21,25 . Finally, it has been reported that SARS‐CoV‐2 can cause abortive infection of macrophages 28,29 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…TMPRSS2 is the principal protease that cleaves the S2’ Spike site required for fusion, but other proteases such as TMPRSS4 and TMPRSS11 may also function in that role 26,27 . Nevertheless, the lack of infection in our model argues against alternative entry pathways, and is consistent with findings reported by others using different macrophage cell models 21,25 . Finally, it has been reported that SARS‐CoV‐2 can cause abortive infection of macrophages 28,29 .…”
Section: Discussionsupporting
confidence: 90%
“…CD147 has been implicated as a pathway for SARS‐CoV‐2 entry, 23 but this is controversial 24 . Antibody‐dependent enhancement can lead to macrophage infection by some viruses in the absence of receptor expression, although evidence for this in SARS‐CoV‐2 is currently lacking 25 . TMPRSS2 is the principal protease that cleaves the S2’ Spike site required for fusion, but other proteases such as TMPRSS4 and TMPRSS11 may also function in that role 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…69 It has been reported that there is no macrophage persistence from infection by SARS-CoV-2 and hence no ADE. 70,71 But if the variants are becoming more resistant to lysosomal proteases including Cathepsin G, then more severe infection observed in the variants could be attributed to ADE. As these mutations are present on different lineages, and we have seen many convergent mutations in past with SARS-CoV-2, these strains might be evolving in the same direction.…”
Section: Protease Site Mappingmentioning
confidence: 99%